Optimal Controller Design of Crowbar System for DFIG-based WT: Applications of Gravitational Search Algorithm - Ahmed, Amany Fayz Ali; Elzein, I. M.; Mahmoud, Mohamed Metwally; Ardjoun, Sid Ahmed El Mehdi; Ewias, Ahmed M.; Khaled, Usama (Universitas Ahmad Dahlan, 2025)
The optimal output and efficacy of a doubly fed induction wind generator (DFIG) are dependent on a multitude of uncontrollable components, necessitating the use of an adequate control system. The crowbar system is essential to the system during abnormal events; thus, it requires appropriate control algorithms and enough control settings. This work suggests the gravitational search algorithm (GSA) to construct the crowbar controller. A synopsis of wind energy and a conversation about the pertinent DFIG component and its methodology. The outcomes acquired with the suggested optimized crowbar system are contrasted with those obtained with a traditional crowbar and without protection. The outcomes confirmed the higher performance of the suggested strategy. The DFIG system responds marginally improved to active and reactive (P&Q) power, DC-Link voltage (DCLV), and machine rotation when a GSA-based PI controller is used. Finally, it can be said that by maintaining the DCLV below the allowable value, which permits the high penetration possibilities of wind energy, the suggested technique assures fault ride-through capacity (FRTC).